Implementation of Problem Formulation Management in Improving the Quality of Research in Higher Education - Nirmalasari, Leli; Harahap, Eka Purnama; Faradilla, Fitri (Pandawan, 2018)
Basically in conducting a study there are problems that can be used as a means toachieve a goal or goal in the study. Everyone who conducts research must have their ownmethod, concept, or method in formulating the problem that is the object of the research. In thispaper will explain the techniques or ways that can be done in relation to formulating problems inresearch including determining a topic to be discussed in research, making backgroundproblems, explaining problem identification, limiting the scope of research, determiningproblems that are worthy of research, making questions in research, and determine the goals,benefits, and uses of the research. With the concept of planning and mature thinking toformulate and determine the formulation of the problem, it is expected that the research that willbe conducted will be focused and directed so that it does not extend to the discussion that is notthe topic of his research. With the formulation of this problem also the reader becomes aware ofthe results and objectives to be conveyed in a study. Therefore in this study we will discuss thesteps or ways in preparing the formulation of a problem that is good and right in order tofacilitate the implementation of a research activity.